Lagenorhynchus albirostris: Information - Barbara Lundrigan (author), Michigan State University: February, 2000; Diana Tarr (author), Michigan State University: February, 2000 (University of Michigan - Animal Diversity Web, 2000)
Lagenorhynchus albirostris: Information